Inside Cover: Improving the Solubility of Artificial Ligands of Streptavidin to Enable More Practical Reversible Switching of Protein Localization in Cells (ChemBioChem 4/2017). (6th February 2017) - Tachibana, Ryo; Terai, Takuya; Boncompain, Gaelle; Sugiyama, Shigeru; Saito, Nae; Perez, Franck; Urano, Yasuteru
Abstract : The inside cover picture shows an improvement in the solubility of artificial ligands of streptavidin (ALiS). The previously reported compound, ALiS‐1 ( ninja at front), cannot access streptavidin (SAv, gold treasure) in cells because of poor water solubility in the absence of organic cosolvent such as DMSO ( samurai ). On the other hand, the new compound, ALiS‐3 (the other ninja ), has higher solubility in water and can reach SAv inside cells; this is represented by his tricky art of escape from the samurai by using water ( suiton‐no‐jutsu ). Picture by R.T. More information can be found in the communication by Takuya Terai, Yasuteru Urano et al. onpage 358 in Issue 4, 2017 (DOI:10.1002/cbic.201600640 ).